Product market competition, ultimate controlling structure and related party transactions - Shenglan Chen; Kun Wang; Xiaoxue Li (China Journal of Accounting Research, 2012)
Previous studies have shown that product market competition has an important effect on corporate strategies and internal governance mechanisms. Using a sample of China's listed firms from 2004 to 2009, we explore the relationship between product market competition and normal related party transactions and find a significant positive relationship. In addition, we investigate the substitutive effect of product market competition and the cash flow rights owned by ultimate controlling shareholders on the extent of normal related party transactions. In particular, our results suggest a positive relationship between the ultimate controlling shareholders' cash flow rights and normal related party transactions that is strongest in noncompetitive industries and weakens as product market competition increases.
Keywords: G32; G34; L14; 650; Product market competition; Ownership structure; Ultimate controlling shareholder; Cash flow rights; Related party transactions